PENERAPAN PROGRAM LINEAR SEBAGAI STRATEGI EFISIENSI PRODUKSI PADA USAHA MARTABAK TRADISIONAL RITEY - Nita Anggriani; Syeren Kowaas; Asmita Masloman; Rygel Angkaa N. Marthing; Maria G. H Wehantow; Julyan Davino A. Salarupa; Imanuek G Kalaena (SOSCIED, 2026)
This study aims to determine the most profitable production combination for the traditional martabak business in Ritey Village by utilizing the simplex method as an analytical tool. The business faces constraints related to raw materials, capital, and production time, which directly affect the number and types of martabak produced daily. Using a descriptive quantitative approach, real data were collected through field observation and interviews, including production time, raw material usage, production costs, and net profit for the three types of martabak produced. These data were then formulated into a linear programming model to maximize profit. The results show that the optimal production combination is achieved at , , and , yielding a maximum daily profit of Rp240,000. The findings reveal a clear difference between the intuitive production decisions previously made by the business owner and the optimal strategy generated through mathematical analysis. This study demonstrates that the simplex method can serve as an effective and practical strategy for small-scale traditional culinary enterprises to enhance production efficiency without altering the product’s traditional characteristics and flavor.